2018
DOI: 10.1007/s00190-018-1223-2
|View full text |Cite
|
Sign up to set email alerts
|

Processing of GNSS constellations and ground station networks using the raw observation approach

Abstract: This article describes the raw observation approach as implemented at Graz University of Technology to determine GNSS products like satellite orbits, clocks, and station positions. To assess the performance of the approach, 15 years (2003-2017) of observations from a network of 245 globally distributed IGS stations to the GPS constellation were processed on a daily basis using the IGS14 reference frame and antenna calibrations. The resulting products are evaluated against those determined by IGS analysis cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 36 publications
1
26
0
Order By: Relevance
“…Since these are experimental products, they are not publicly available currently. Unlike all other satellite products relying on the IF LC, TUG products are calculated using a raw observation approach (Strasser et al 2018). Therefore, this product is suitable for fixing any linear combination, whereas all other products enable PPP-AR only for the IF LC of two specific frequencies.…”
Section: Observation Modelmentioning
confidence: 99%
“…Since these are experimental products, they are not publicly available currently. Unlike all other satellite products relying on the IF LC, TUG products are calculated using a raw observation approach (Strasser et al 2018). Therefore, this product is suitable for fixing any linear combination, whereas all other products enable PPP-AR only for the IF LC of two specific frequencies.…”
Section: Observation Modelmentioning
confidence: 99%
“…In the measurement models, the unknowns include not only the coordinate parameters, but also the time delays caused by the atmosphere and device hardware, as well as the ambiguities for phase measurement. In relative positioning, the hardware delays can be nonzero values and should be considered in multi-GNSS and GLONASS data processing, i.e., inter-system bias (ISB) [9,10,26] and inter-frequency bias (IFB) [27], respectively. The ISB and IFB of the measurements are correlated with the ambiguities and are the key problems to be solved.…”
Section: Mathematic Models Of Gnss Precise Data Processing and The DImentioning
confidence: 99%
“…The Gravity Recovery Object Oriented Programming System (GROOPS) used at IfG is a software suite for geodetic applications. Its feature set includes the determination of GNSS orbits, clocks and ground station networks (Strasser et al, 2019), static and time-variable gravity field solutions from satellite data, and regional gravity field modeling with terrestrial data. GROOPS is written in C++ and makes heavy use of low level Basic Linear Algebra Subprograms (BLAS) and LAPACK (Linear Algebra PACKage) subroutines.…”
Section: Groopsmentioning
confidence: 99%
“…As the example of several services, like the International GNSS Service (Johnston et al, 2017) and the International Laser Ranging Service (Pearlman et al, 2002), showed, combining solutions from various institutions, which are computed by different and independent software packages, leads to improved results. The COST-G initiative was formally established in 2019 and op-M. Lasser et al: Benchmark data for verifying background model implementations erationally provides state-of-the-art monthly global gravity models from the Gravity Recovery And Climate Experiment (GRACE, Tapley et al, 2004), GRACE Follow-On (Landerer et al, 2020) and Swarm (Friis-Christensen et al, 2006). COST-G is a product centre of the International Gravity Field Service (IGFS) under the umbrella of the International Association of Geodesy (IAG).…”
Section: Introductionmentioning
confidence: 99%